Copyright Protection for Dance Creators New Creations - Dina Karlina; Syarif Muhammad Ikhsan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze copyright protection for the creators of new dance creations in Pontianak City. In the context of copyright protection, the registration of new dance creations, which are categorized as works of art reflecting local cultural identity, is a key step in preventing plagiarism or unauthorized use of works and the resulting damages. Through a normative empirical approach and data collected through interviews and literature studies, it was found that awareness of the importance of copyright exists, but knowledge about the mechanisms and benefits of copyright registration for new dance creations is not yet optimal. The results of this study are expected to enhance understanding of copyright protection and serve as a bridge for the government to gradually and selectively disseminate information.. The main obstacle faced by new creation dance creators in Pontianak City is the lack of knowledge and awareness about the mechanism of copyright registration and the benefits obtained from such registration. Many dance creators find the registration process complicated and expensive, so they are not interested in registering the copyright of their work. In addition, socialization from the government regarding the importance of copyright and how it is recorded.